Performance of Islamic Stocks Index: Comparative Studies Between Indonesia and Malaysia - Tulasmi Tulasmi; Rianto Rinda Trihariyanto (Signifikan: Jurnal Ilmu Ekonomi, 2016)
The aim of this research is to compare the Islamic stocks index performance between Malaysia and Indonesia using Sharpe method, Treynor method, and Jensen method. The result show that the Islamic stocks index performance in Indonesia –measured by Jakarta Islamic Index- is better than Malaysia if using Treynor and Jensen methods. Otherwise, using the Sharpe method show that Islamic stock index in Malaysia is better than Islamic stocks index in Indonesia. The implication from this result is the investor with enough funds recommended to invest in Indonesia, but the small investor can do the investment to Islamic stocks index in Malaysia.DOI:  10.15408/sjie.v5i1.3127